“Gen Z Malas dan Gampang Resign?”: Analisis Wacana Kritis atas Representasi Negatif dalam Media Massa - Gaza, Muhammad (UI Scholars Hub, 2025)
This study employs Norman Fairclough’s Critical Discourse Analysis to examine how Indonesian online media construct negative stereotypes of Generation Z in the workplace. Based on an analysis of 15 national news articles (January–May 2025), the findings reveal that narratives such as “lazy,” “spoiled,” and “quick to resign” are consistently reproduced through word choice, institutional quotes, and framing aligned with traditional work values. The discourse operates on three levels: micro (biased linguistic structures), meso (digital market logic), and macro (intergenerational value tensions). These representations are not mere reflections of reality but symbolic practices that reinforce dominant work structures. A critical reading of media discourse and the creation of more inclusive workplaces for younger generations are urgently needed.